1968
DOI: 10.2134/agronj1968.00021962006000050018x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rainfall and Temperature Interactions During the Growing Season on Corn Yield1

Abstract: Maximum daily temperatures and rainfall were found to have a large effect on corn yield from 25 days before to 15 days after anthesis. This corresponds to the average calendar interval of June 30 through August 8 at Urbana. The maximum effect of temperature and rainfall on corn yield occurs approximately one week before anthesis and remains at a high level one week to either side of the maximum. The models solved in this investigation indicate that high temperatures (maximum daily temperatures between 32.2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 0 publications
0
49
1
1
Order By: Relevance
“…Soil moisture in the spring and early summer is necessary for nitrogen (N) mineralization. Timing of precipitation also is important; for example, rainfall is critical with respect to maize yields during the week preceding and the week following anthesis when male flowering and pollen shed begin (Runge 1968).…”
Section: On-field Precipitationmentioning
confidence: 99%
“…Soil moisture in the spring and early summer is necessary for nitrogen (N) mineralization. Timing of precipitation also is important; for example, rainfall is critical with respect to maize yields during the week preceding and the week following anthesis when male flowering and pollen shed begin (Runge 1968).…”
Section: On-field Precipitationmentioning
confidence: 99%
“…Crop yields are one of the most utilized indicators of the impact of weather during the growing season, and county, state, and national yields have been extensively used to evaluate weather effects through statistical and simulation models. An example of statistical analysis approaches are provided in Runge (1968), Muchow et al (1990), Lobell (2007, Lobell and Field (2007), and Hatfield et al (2011) in which different parameters, e.g., temperature, precipitation, or solar radiation, have been related to the variation in crop yield among years. The use of simulation models to assess future effects of projected climate has been reported in Lobell et al (2006) and Hatfield et al (2011), and there are ample references detailing the utility of different methods.…”
Section: Crop Progress and Productivitymentioning
confidence: 99%
“…Muchow et al (1990) showed that simulated yields in the central Corn Belt decrease by 5% to 8% per 2°C temperature increase. Runge (1968) reported that observed corn yields are affected by interactions between maximum daily temperature and rainfall from 25 days before to 15 days after anthesis. Izaurralde et al (2003) indicated that dryland corn yields in the Corn Belt are predicted to increase by about 8.3% in the period around 2095 with CO 2 effects under HadCM2 scenarios.…”
Section: Uncertainty Of Changes In Yield Climate Change Impactsmentioning
confidence: 99%